Teachers' Efforts in Islamic Religious Education to Improve Students' Understanding of Islamic Cultural History Material at Al-Ulum Integrated Islamic Junior High School Medan - Hafizhah Najwa Tanjug; Muhammad Basri (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to determine the efforts of Islamic Religious Education teachers in improving students' understanding of Islamic Religious Education (ISK) material at Al-Ulum Terpadu Medan Middle School and to identify supporting and inhibiting factors in the learning process. The study used a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The results indicate that Islamic Religious Education teachers make various efforts to improve students' understanding, such as utilizing learning media such as PowerPoint and projectors, using storytelling methods, and implementing group discussions in the learning process. These efforts help students understand the material more easily, increase their interest in learning, and create a more active and engaging learning environment. Supporting factors in learning include the availability of school facilities and infrastructure and high student interest in learning, while inhibiting factors stem from differences in student characteristics and learning styles in understanding the material.